ANALISIS DIALOG ROLE PLAY TENTANG RESERVASI HOTEL DITINJAU DARI TAKSONOMI BLOOM: Analysis of Role Play Dialogue on Hotel Reservations Reviewed from Bloom's Taxonomy - Nirwani, Ayulia (ABISATYA DINAMIKA ISWARA, 2025)
ABSTRACT This study aims to analyze the implementation of role-play dialogues on the reservation process during guest check-in at the hotel front office, using Bloom’s Taxonomy framework, which covers the cognitive, affective, and psychomotor domains. The research employed a descriptive approach by observing role play activities conducted in the Front Office course. The findings show that, in the cognitive domain, students were able to understand concepts and apply check-in procedures in accordance with standard operating guidelines. In the affective domain, students demonstrated professionalism, hospitality, and the ability to build positive interactions with guests. Meanwhile, in the psychomotor domain, students displayed practical skills in effective communication, operating work equipment, and performing reservation procedures accurately. Overall, the application of the role play method proved effective in integrating knowledge, attitudes, and skills, thereby supporting the achievement of more comprehensive learning outcomes in the front office field. Penelitian ini bertujuan untuk menganalisis pelaksanaan dialog role play mengenai proses reservasi pada saat check-in di front office hotel dengan menggunakan kerangka Taksonomi Bloom yang mencakup ranah kognitif, afektif, dan psikomotorik. Penelitian ini dilakukan melalui pendekatan deskriptif dengan mengobservasi aktivitas role play yang diterapkan dalam pembelajaran mata kuliah Front Office. Hasil analisis menunjukkan bahwa pada ranah kognitif, mahasiswa mampu memahami konsep serta menerapkan prosedur check-in sesuai standar operasional. Pada ranah afektif, mahasiswa memperlihatkan sikap profesional, keramahan, serta kemampuan membangun interaksi positif dengan tamu. Sementara itu, pada ranah psikomotorik terlihat keterampilan mahasiswa dalam berkomunikasi secara efektif, mengoperasikan perangkat kerja, dan melaksanakan prosedur reservasi dengan ketepatan yang baik. Secara keseluruhan, penerapan metode role play terbukti efektif dalam mengintegrasikan aspek pengetahuan, sikap, dan keterampilan, sehingga mendukung pencapaian hasil belajar yang lebih komprehensif pada bidang front office.